Systematics of the seed beetle genus Decellebruchus Borowiec, 1987 (Coleoptera, Bruchidae) - Nápoles, Jesús Romero (Zookeys, 2016)
Abstract. Keys to species, descriptions, synonymy, host plants, and geographical distributions are presented for the three species in the genus Decellebruchus (Borowiec 1987); of those, Decellebruchus walker (Pic 1912) was the only species included at the time of the genus denomination, Decellebruchus atrolineatus (Pic 1921) is transferred to this genus, and Decellebruchus lunae is described as a new species. The shortest and most parsimonious phylogenetic tree for genera with pectinate antennae had a length of 33, consistency index 87, and retention index 81.